Analisis Antrian Penjualan Pada UMKM Kebab KZL Aek Tapa - Chahira, Mayang; Silvana, Mega; Huda, Nurul; Yusfina, Yusfina; Ritonga, Irmayanti (Universitas Labuhanbatu, 2025)
This article presents an analysis of the queuing system of UMKM Kebab KZL Aek Tapa with the aim of determining the optimal waiting time. This research uses observation and literature review methods to collect waiting time and service data. In the context of Kebab KZL, the queuing system used is a single channel model (M/M/1). Perform queue analysis using QM for Windows software to understand customer arrival and service trends. The analysis results show that the average waiting time of customers in the queue is 13 minutes, and the service utilization rate is 62%. These insights are expected to help UMKM Kebab KZL in improving the efficiency of the queuing system and service to customers.